Mercury contamination of fish and exposures of an indigenous community in Par? state, Brazil - Brabo, Edilson da Silva (Elsevier, 2021)
Fish consumption is an important source of protein among indigenous communities in Amazonian Brazil. Exposures to mercury via fish were studied in an indigenous community of the Munduruku reserve, located in the Tapaj?s River basin in the state of Par?, one of the oldest and most productive gold mining areas in the Amazon region. This study summarizes the results of mercury (Hg) analyses of fish consumed by inhabitants of the Munduruku settlement of Sai Cinza. The most frequently consumed fish, reported by 330 persons interviewed for this study, were tucunar?, pacu, jaraqui, tra?ra, aracu, matrinch?, and caratinga. The mean mercury concentration in carnivorous fish was 0.297 microg.g(-1) while in noncarnivorous fish mean mercury concentration was 0.095 microg.g(-1). Only in caratinga was there a significant relationship between fish size, weight, and mercury levels. Levels of methylmercury in the tucunar? averaged 0.170 microg.g(-1), while in tra?ra the mean level of methylmercury was 0.212 microg.g(-1). Although the levels of Hg in fish consumed by the Sai Cinza community are below the Brazilian limit value for consumption, the high rates and amounts of fish consumed by this population are relevant to evaluating risks of mercury contamination for communities with limited food resources.